(untitled) (International Journal of Food and Nutritional Sciences, 2022)
“Web Mining” - knowledge extractor from the huge repository i.e. World Wide Web. It uses the data mining techniques to extract the valuable, needful information from the internet. The various types of information are required to enhance the profit, to get popularity, to take wise decisions. All this type of data is gathered from web content, web structure and web usage data by using the web mining techniques. Because of providing large, very essential information, the web mining gets the popularity very fast among researchers and users. So in today’s world, where required data is available and accessible to all easily, then Why not to use it for our benefit? In this paper web mining and its applications in real world for sustainable development are discussed.